From Tradition to Market: A Study of the Design Application of "Jiama" Images in Souvenirs - Pengchuan, Huang; Sirivesmas , Veerawat; Rueanglada , Kwan (Journal of Roi Kaensarn Academi, 2024)
This study aims to explore the innovative application and commercialization pathways of images from the traditional Bai ethnic craft “Jiama” in the design of modern tourism souvenirs. Focusing on “Jiama” images, the study combines design practice cases to analyze the potential and value of traditional cultural symbols in contemporary tourism souvenir design. Guided by innovation and practicality, the study selects several design works based on “Jiama” images as samples, with market feedback serving as a key evaluation criterion, it is a qualitative research. Research instruments include questionnaire, data collection, literature reviews, expert interviews and data analysis to obtain multidimensional research information. The analysis adopts a combination of qualitative and quantitative methods to systematically demonstrate the practical effects of “Jiama” images in terms of design strategies, craftsmanship implementation, and market performance. The research results found that indicate that integrating traditional cultural elements into modern design provides a feasible path for the contemporary revitalization of cultural heritage while showcasing its market potential and cultural value. Through the innovative design and application of “Jiama” images, the research successfully transforms cultural symbols, originally confined to traditional contexts, into modern products that combine practicality and artistry. This transformation further enriches the content and form of Yunnan’s ethnically distinctive tourism souvenirs, promoting the synergistic development of cultural and creative industries with the local tourism economy. Compared to existing studies, this research not only verifies the practical value of traditional cultural symbols in modern design but also offers new references for the development of similar cultural resources worldwide. These practical experiences provide insights into the transformation of traditional cultural resources in other regions and offer theoretical support for designers and practitioners exploring new ways to integrate culture and markets.